تطوير استغلال الثروات النهرية المشتركة مع دول الجوار - عباس، سجى محمد; حمزة، غزوان جاسم (الجامعة المستنصرية - مركز المستنصرية للدراسات العربية والدولية, 2021)
إن الأنهار الدولية مصدر وثروة للدول وهي وسيلة للنقل لتوفير مستلزمات الحياة الإنسانية، وقيام دول الجوار بالاستحواذ والسيطرة على الأنهار الدولية دون موافقة الدول المشتركة يشكل انتهاكا لقواعد القانون الدولي والمعاهدات الدولية، كما يؤثر على حياة الإنسان وحقوقه الأساسية في النقل والصحة والاستثمار الزراعي والصناعي، إضافة إلى الاستقرار بين الدول. International rivers are a source and wealth for states, and they are a means of transport to provide the requirements of human life. Neighboring countries' acquisition and control of international rivers without the consent of the participating countries is a violation of the rules of international law and international treaties, and affects human life and basic rights in transport, health, agricultural and industrial investment, in addition to Stability between nations.
Keywords: الأنهار الدولية -- القانون الدولي -- القوانين والتشريعات